From Treatise to Test: Evaluating Traditional Remedies for Anti-Biofilm Potential - Kadam, Snehal; Madhusoodhanan, Vandana; Bandgar, Anuradha; Kaushik, Karishma S. (Frontiers in Pharmacology, 2020)
Traditional plant-based remedies hold vast potential as novel antimicrobial agents, particularly for recalcitrant infection states such as biofilms. To explore their potential, it is important to bring these remedies out of historical treatises, and into present-day scientific evaluation. Using an example of Indian traditional medicine (Ayurveda), we present a perspective toward evaluating historical remedies for anti-biofilm potential. Across compendia, we identified three plant-based remedies (of Kalanchoe pinnata, Cynodon dactylon, and Ocimum tenuiflorum) recommended for wounds. The remedies were reconstituted in accordance with historical practices, and tested for their effects on biofilm formation and eradication assays of wound pathogens, Pseudomonas aeruginosa and Staphylococcus aureus. Based on our approach and the results obtained, we provide insights into the considerations and challenges related to identifying potential remedies in historical texts, and testing them in the laboratory with standard biofilm assays. We believe this will be relevant for future studies exploring anti-biofilm approaches at the interface of historical medicine and present-day scientific practices.